Oxygenation of copper(I) complexes containing fluorine tagged tripodal tetradentate chelates: significant ligand electronic effects. Issue 11 (28th October 2022) - Li, Runzi; Khan, Firoz Shah Tuglak; Tapia, Marcos; Hematian, Shabnam
Abstract: Copper-dioxygen (O2 ) interactions are of great importance in biological and chemical transformations involving reversible dioxygen binding, activation, or reduction. In this report, we describe O2 -reactions with the mononuclear copper(I) complexes containing two new analogues of the known nitrogen-containing tetradentate tripodal chelate, tris [(2-pyridyl)methyl]amine (TMPA). In both derivatives, one electron-rich and one electron-deficient, fluorine atoms are attached to the ligand framework, allowing for the use of 19 F-NMR spectroscopy to probe the oxygenation process. Variations of ligand electronic properties are manifested in the electrochemical behavior of copper complexes and their reactivities toward O2 . Our NMR spectroscopic studies, along with variable-temperature electronic absorption measurements, revealed that the copper(I) complexes reversibly react with O2 to form the corresponding 1:1 copper-O2 (i.e., end-on superoxo) intermediates which can further react reversibly with second equivalents of copper(I) complexes to form the related dinuclear 2:1 copper-O2 (i.e., trans- peroxo) adducts. However, considerable differences exist in detail at various temperatures, depending on the chelate. All three end-on superoxo and trans- peroxo species described here possess similar spectroscopic features, although small but significant shifts in the energy of their signature bands were observed, suggesting that the variation in the chelates directly affects the electronic properties of the copper-O2 cores. Graphical Abstract: UF0001